Evaluating Educational Programs: A Planning Tool - Deborah Sleight (Association of American Medical Colleges, 2007)
Abstract This is an introductory-level web-based tutorial that guides users through the six steps to developing an evaluation plan for their program or curriculum. The six steps are as follows: (1) state the program goal, (2) state the program objectives, (3) write the program description; (4) list the program evaluation questions, (5) list the sources of evaluation data, and (6) describe the methods of data collection. The evaluation planning tool that accompanies this tutorial is a table with six columns, one for each step. The table helps users make the content of each step consistent with the content of the other steps. Users can print this tool out and fill it in by hand or can enter text into the electronic version and save it on their computer. The tutorial includes two examples of completed evaluation planning tools, one of which is a running example whose columns are filled in during the explanation of each step. These examples were adapted from programs related to health professions education appearing as published articles. After completing the tutorial, users will have a plan that summarizes all the important components of their evaluation in an organized structure. Some educational programs are rarely evaluated for effectiveness, learner satisfaction, or how well they accomplish their educational objectives. This tutorial guides users in preparing an evaluation plan that they can then implement. Users can also include their evaluation plan in grant proposals to strengthen them.